Global urbanism. Knowledge, power and the city. - (:unkn) unknown (Routledge, 2021)
Global Urbanism is an experimental examination of how urban scholars and activists make sense of, and act upon, the foundational relationship between the ‘global’ and the ‘urban’. What does it mean to say that we live in a global-urban moment, and what are its implications? Refusing all-encompassing answers, the book grounds this question, exploring the plurality of understandings, definitions, and ways of researching global urbanism through the lenses of varied contributors from different parts of the world. The contributors explore what global urbanism means to them, in their context, from the ground and the struggles upon which they are working and living. The book argues for an incremental, fragile and in-the-making emancipatory urban thinking. The contributions provide the resources to help make sense of what global urbanism is in its varieties, what’s at stake in it, how to research it, and what needs to change for more progressive urban futures. It provides a heterodox set of approaches and theorisations to probe and provoke rather than aiming to draw a line under a complex, changing and profoundly contested set of global-urban processes.
Keywords: Urbanismus; Globalisierung; Verstädterung; Interdisziplinarität; Stadtforschung; Forschungsaufgabe; Forschungsansatz; Internationaler Vergleich; Urban Governance; Wissensbasis; Klimawandel; Migration; Sozialer Konflikt; Transformation; Fallbeispiel; Lehrbuch